Pengaruh Pemberian Latihan Soal Dengan Tuntunan Penyelesaian Dalam Pembelajaran Langsung Terhadap Peningkatan Pemahaman Konsep Hukum Perbandingan Tetap Pada Siswa Kelas X SMA Negeri 4 Palangka Raya Tahun Ajaran 2018/2019 - Sela Anjelia (FKIP Universitas Palangka Raya, 2020)
The purpose of this study is to explain the effect of providing guidance on solving exercises in direct learning towards understanding the concept of fixed comparative law (Proust Law) in Class X Students of SMA Negeri 4 Palangkaraya in the academic year 2018/2019. This type of research is quantitative research. Researchers conduct experiments by determining samples for the control class and the experimental class. Research subjects were 71 grade X students of SMA Negeri 4 Palangka Raya City in 2018/2019 school year. The instrument used was in the form of concept understanding tests (test I and test II) in the form of essays totaling 4 questions and practice questions with completion instructions which were packaged in the form of question sheets containing the steps of problem solving. Based on the results of statistical tests using the t-test shows that there is a difference in the increase in understanding of the concept of the law of comparative learning outcomes using the exercises with the solution to the completion of the problem using the exercises without the solution to the completion of class X students of SMA Negeri 4 Palangka Raya. The average increase in concept understanding in the n-gain experimental class (73.48%) is higher than the control class (54.57%).